Revealing the relationships between luminous environment characteristics and physiological, ocular and performance measures: An experimental study. (April 2020) - Hamedani, Zahra; Solgi, Ebrahim; Hine, Trevor; Skates, Henry
Abstract: This study examined human subjects and their physiological, ocular and performance responses under different lighting conditions. The experiment was carried out in an office with daylight as its primary light source. Physiological and ocular data which were recorded by eye-tracking glasses included mean Pupil Diameter (PD), Pupillary Unrest Index (PUI), Blink Rate (BR), Blink Amplitude (BA), eye Fixation Rate (FR), and Eye Convergence (EC). Performance measures included Combined Visual Performance (CVP) and Combined Reading Performance (CRP), both critical for office workers' overall performance and productivity at workstations. Correlation and multiple regression analysis were used to determine the relationships between glare factors and the physiological, ocular and performance measures. Data analysis suggests that PUI, BA, FR and mean PD could be used as a visual discomfort proxy. PUI and BA could be predicted better with relative glare factors (contrast), and FR and PD could be predicted better with the absolute glare factors (luminance and illuminance values). Concerning performance measures, this study identified that the CVP was negatively correlated with vertical illuminance at eye level and the average luminance. The CRP was also better when the PUI was lower. Highlights: The relationships among glare factors and physiological, ocular and performance measures were investigated. Blink Amplitude and Pupillary Unrest Index were predicted better with relative glare factors. Fixational eye movements and Pupil Diameter were predicted better with absolute glare factors. Eye convergence was not affected by lighting conditions.